Experimental investigation of a diesel engine using waste plastic oil blends - Norkhizan, A. M.; Ahmad Fitri, Yusop; Mohd Adnin, Hamidi (Springer, 2023)
Plastic have now become essential materials in the present world and implimentation in the industrial field is persistently rising. The aim of this project is to investigate the effects of waste plastic oil on engine performance and pollutant emissions. The engine test was conducted under constant engine speed of 1800 RPM and varies engine load of 20%, 40% and 60% respectively. The performances of engine were analyzed in term of brake power (BP), brake specific fuel consumption (BSFC) and brake thermal efficiency (BTE). The effect of WPO on brake power was only dominant during low and medium engine load condition. WPO can reduce the BSFC of diesel engine except for high load condition. In addition, the formation of NOx and CO for WPO fuel blends were greater than D100 under all engine load conditions. Therefore, in conclusion, the implementation of WPO in diesel engine can improve engine performance but limit its effectiveness in terms of pollutant emissions.